“The Intentional Fallacy”, itself a Fallacy: a Critique of Wimsatt and Beardsley’s “The Intentional Fallacy” - Sareh Khosravi (Language Art, 2021)
Abstract This research aims to highlight the falsities of William K. Wimsatt and Monroe C. Beardsley’s article “The Intentional Fallacy” (1946). These two New Critics believe that the intention of the author should not be considered when judging the text because the intention of the author is neither available nor desirable. The present research questions two of their claims: that the intention is something separate from the textual meaning and that the authorial intention is private and biographical while the poem is public. To refute their claims, the research employs E.D. Hirsch’s concept of verbal meaning. Verbal meaning is simply a special kind of intentional object which he considers to be synonymous with textual meaning. The study goes beyond Hirsch’s ideas and claims that from the moment the author transfers his intention, through language, to the text, it is no longer an intention but the object. Language, according to the New Critics is a proper and reliable medium, so when Wimsatt and Beardsley question the authorial intention, they are actually questioning the very notion of language. Their second claim, that is the private nature of the author’s intention, will be rejected by borrowing T.S. Eliot’s analogy of the poet to a catalyst. Eliot shows that the poet does not include his/her personality traits in the poem. The achievement of this study is a new view toward the authorial intention, a view which is not based on personal and biographical factors but on verbal factors.